THE VALIDITY OF SCIENTIFIC LITERACY-BASED LKPD INTEGRATED VERSES OF THE QURAN WITH LIGHT MATERIAL FOR MTS STUDENTS - Indana Fitriyati Maghfiroh; Noer Af’idah (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
21st century education requires students to master 4C skills (creativity, critical thinking, collaboration, communication). Learning indicators with mastery of 4C skills can be obtained through the development of student worksheets (LKPD) based on integrated scientific literacy of Al Quran verses. One of the scientific literacy-based learning related to real life is the material of light. This research is a development research. The purpose of this study is to describe the process and result of developing LKPD based on integrated scientific literacy of Al Quran verses based on validity tests. In this LKPD development research, using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) without using the implementation stage. After being developed, LKPD based on integrated scientific literacy of Al Quran verses were validated by expert validators, namely media expert lecturers, material expert lecturers, and science teachers. Data analysis used quantitative descriptive. The result of the LKPD validation assessment based on scientific literacy integrated verses of the Al Quran on light material obtained an average score of 3,84 including the very valid category. Based on the result of this study, the scientific literacy-based LKPD integrated verses of the Al Quran on light material developed has been declared feasible to be applied during the learning process.